Microbial transformation of soil organic matter under varying agricultural management systems in Ukraine - Symochko, Lyudmyla; Demyanyuk, Olena; Crisan, Vlad; Dinca, Lucian (Frontiers in Microbiology, 2024)
This paper presents comparative studies on the content and structure of organic matter (OM) and the activity of microbiological cellulose destruction in three types of Ukrainian soils intensively used in agricultural production. The highest content of humus in the arable layer (4.9%), OM (410 t ha -1 ), and total carbon (30.9 mg С g −1 soil) was determined in chernic phaeozems, which is 2.2-2.5 times higher than in albic retisols. The soil of natural ecosystems is characterised by a high content of microbial carbon (Cmic) in the carbon fraction of organic soil compounds. In arable soils, the content and reserves of humus and soil organic matter (SOM) have decreased by an average of 1.5-2 times. The most considerable loss of humus reserves in the soil profile was identified in albic retisols (1.96-1.44 times) and the smallest in chernic phaeozems (1.27-1.81 times). During the long-term systematic application of mineral fertilisers, the Corg content decreased by 8-21% in chernic phaeozems, 12-33% in greyzemic phaeozems, and 6-38% in albic retisols. A significant difference of 2.1-8.0 times was determined regarding the number of aerobic cellulolytic microorganisms and 1.3-3.3 times in the potential cellulolytic activity of the studied soils. The high number of cellulosedestroying microorganisms is characteristic of chernic phaeozems with a high content of OM in the soil; the advantage over other types of studied soils was 1.4 times and 7.8 times for greyzemic phaeozems and albic retisols, respectively. Among the studied soil types, high values of CO2 emissions were identified in chernic phaeozems. Intensive agricultural practices in Ukrainian soils have significantly altered the content and composition of organic matter, leading to reduced humus and soil organic matter reserves. The study also underscores the importance of considering the abundance of cellulose-destroying microorganisms and their potential activity in assessing soil health and sustainability.